All-glass vacuum tube heat transfer simplified model. (November 2019) - Ardila, O; Quiroga, J; Martínez, O
Abstract: This paper addresses the design of an algorithm that estimates the irradiance and the selective layer temperature of the all-glass vacuum tube as a function of the ambient temperature in Bucaramanga, Northern Colombia. A Matlab code to meteorological National Aeronautics and Space Administration data processing and to find a linear relationship between the irradiance and ambient temperature on the location of study, was developed. The behavior of this relationship for several hours of the day was studied, and it was found that it is possible to use this relationship as a reliable preliminary approach in water heating systems design using all-glass vacuum tube. This facilitates the design calculations and would encourage the use of solar energy in water heating systems in Colombia.